Ultrasound-guided core biopsy in the diagnostic work-up of tuberculous lymphadenitis in Saudi Arabia, refining the diagnostic approach. Case series and review of literature - Othman Altuwairgi; Salim Baharoon; Yosra Alkabab; Eiman Alsafi; Mohammed Almoweqel; Hamdan AL-Jahdali (Elsevier, 2014)
Summary: Objective: Tuberculous cervical lymphadenitis is the most common presentation of extrapulmonary tuberculosis (TB) in Saudi Arabia and worldwide. Obtaining a tissue biopsy for culture and histopathology is frequently needed to establish the diagnosis. The available diagnostic tools include excisional surgical biopsy, fine needle aspiration (FNA) and ultrasound-guided core lymph node biopsy. We present a single center experience of the use of ultrasound-guided core lymph node biopsy as a diagnostic tool for tuberculous lymphadenitis. Methods: A retrospective review of the interventional radiology database for all of the patients with cervical lymphadenopathy undergoing ultrasound-guided core biopsy at King Abdulaziz Medical City-Riyadh, Saudi Arabia from January 1 2008 to December 30 2011. The data were the patient demographics, clinical characteristics, biopsy method and pathological and clinical diagnoses. Results: Five cases underwent ultrasound-guided cervical lymph node biopsy during the study period. A total of 55 cases underwent excisional cervical lymph node biopsy in the same period. The age of the patients who underwent the core biopsy ranged from 18 to 76 years old. All of the biopsies were performed as one-day surgery, and all of the patients were discharged on the same day with no complications. The final diagnosis was confirmed in all of the cases (100%); with tuberculosis being the diagnosis in four of the five cases (80%), and one case being diagnosed as lymphoma. Conclusion: Ultrasound-guided core biopsy is an underutilized procedure in our hospital and could be a very valuable asset in the diagnostic algorithm of tuberculous lymphadenitis in Saudi Arabia. The widespread use of the procedure would positively affect patient care, providing earlier diagnosis and treatment. Keywords: Ultrasound-guided biopsy, Ultrasound-guided core biopsy, Ultrasound-guided lymph node biopsy